A socio-ecological and multicultural approach to artistic education that uses local heritage as a means of learning: Girona, Temps de flors. - Calbó Angrill, Muntsa (Pulso. Revista de educación, 2008)
On the occasion of the celebration of the festivities of Girona called Temps de Flors (Flower time), the students of Teacher Training in the Education College in Girona have developed an artistic work in a park of this town. In this project, they had the opportunity to work on artistic, socio-ecological and multicultural contents. More specifically, they have reflected on their own identities as women, have experienced new ways of knowing and feeling an element of the cultural heritage of their surroundings and have solved several artistic problems creatively.